Editorial: Safety and Effectiveness of COVID-19 Vaccines on COVID-19 Infection and Its Long-Term Consequences - Ana Paula Junqueira-Kipnis (Vaccines)
COVID-19 continues to affect people around the world, according to the genomic reports [...]